2002
DOI: 10.1357/00222400260497471
|View full text |Cite
|
Sign up to set email alerts
|

Internal wave band eddy fluxes above a continental slope

Abstract: Three weeks of velocity and temperature measurements from the bottom 45 m above the continental slope in the Bay of Biscay are used to evaluate the role of the internal wave band in boundary mixing near a sloping bottom. Utilizing acoustic Doppler current profilers and thermistor strings, internal wave band eddy fluxes of momentum and heat are estimated. The instrumentation is specifically designed to resolve internal wave band processes. Due to unresolved Doppler shifting, this wave band may include turbulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Efforts over the Mid-Atlantic Ridge (Polzin et al 1997) and Hawaii (Klymak et al 2006) have demonstrated increased dissipation over deep, rough topography. Similar observations have been made elsewhere in a growing body of literature (e.g., Gemmrich and van Haren 2002;Nash et al 2007;Alford et al 2011Alford et al , 2014van Haren and Gostiaux 2012). Progress has also been made in predicting the dissipation observed near topography.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Efforts over the Mid-Atlantic Ridge (Polzin et al 1997) and Hawaii (Klymak et al 2006) have demonstrated increased dissipation over deep, rough topography. Similar observations have been made elsewhere in a growing body of literature (e.g., Gemmrich and van Haren 2002;Nash et al 2007;Alford et al 2011Alford et al , 2014van Haren and Gostiaux 2012). Progress has also been made in predicting the dissipation observed near topography.…”
Section: Introductionsupporting
confidence: 78%
“…Observations have revealed elevated near-bottom mixing at midslope regions that are near critical to the tidal forcing. This enhanced mixing is associated with internal wave propagation onto a critical slope by the setup of borelike structures due to wave reflection (White 1994) or through the collapse of unstable stratification associated with oblique internal waves (Gemmrich and van Haren 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As the model is fully nonlinear, the transfer of energy from the fundamental forcing frequency (namely the inertial frequency) to higher harmonics is also briefly examined. Recent measurements [ van Haren et al , 1999, 2002; Gemmrich and van Haren , 2002] and modeling have shown that this process is important in transferring energy to higher frequencies and eventually turbulence [ Inall et al , 2000]. This process of transferring energy from a fundamental forcing frequency to higher harmonics is well established in tidal modeling in shallow sea regions [e.g., Pingree and Maddock , 1978; Davies and Kwong , 2000, and references therein] and occurs here particularly in the frontal region.…”
Section: Introductionmentioning
confidence: 89%
“…Recent calculations using a three‐dimensional prognostic model forced with the barotropic tide and incorporating a turbulence energy closure scheme have shown that it can reproduce the internal tide and enhanced shelf edge cooling [ New and Pingree , 1990] associated with it [ Xing and Davies , 1996a]. Besides the tides, wind forcing is a major source of mixing, particularly in shallow seas [ Van Haren et al , 1999; Van Haren , 2000] and shelf edge regions, where the continental slope influences the internal wave spectrum [ Van Haren et al , 2002; Gemmrich and Van Haren , 2002]. Recent ideas [ Munk and Wunsch , 1998] suggest that a major part of the mixing in the ocean is due to boundary layer mixing of tidal and wind origin at the shelf edge, which then diffuses into the ocean.…”
Section: Introductionmentioning
confidence: 99%